Effect of Gum Chewing on Prevention of Post - F Akhlaghi; M Pourjavad; A Mansouri; F Tara; M Vahedian (Tehran University of Medical Sciences, 2008)
Background & Aim: Post cesarean ileus is a common complication that induces abdominal distention, delays feeding, and increases hospitalization. Multiple studies showed that false nutrition increases the bowel movement. This study aimed to investigate the effect of gum chewing as false nutrition on the bowel movement and prevention of post cesarean ileus. Methods & Materials: In this randomized controlled trial, a total of 400 patients who were hospitalized in Mashhad Zeinab hospital were divided into two 200-patient groups. The groups were matched for age, gravity and duration of surgery. In the intervention group, gum chewing was started after surgery, 3 times/day until the regular diet was initiated. In the control group, patients underwent routine care by restricting oral intake until the bowel function was returned. The outcomes were time of the first bowel sound, flatus passage, defecation, ambulation of patients post cesarean, initiation regular diet, and hospitalization. Statistical analysis was performed using unpaired t-test and fisher's exact probability test. Results: The mean age, parity and operation time were similar in the two groups. All patients in the intervention group tolerated gum chewing immediately after surgery. The results showed the followings among the intervention group vs. control group, respectively: post operative time intervals to bowel sounds (14.7 hours vs. 16.6 hours; P=0.569), time intervals between surgery and abdominal distention (16.59 hours vs. 14.21 hours; P=0.01), first post operative defecation (28.16 hours vs. 32.21 hours ; P=0.000), post operative time interval to onset diet (19.3 hours vs. 16.54 hours; P=0.000), post operative time interval to ambulation (20.14 hours vs.17.58 hours; P=0.000), post operative lengths of ileus (31.13 hours vs. 30.35 hours; P=0.5), hospitalization (1.84 days vs. 1.92 days; P=0.02). Conclusion: Gum chewing after cesarean section is safe and well tolerated and reduces post operative ileus, shortens mean duration of first defecation, decreases the time of returning to regular oral diet, shortens the time of patient ambulation and hospital discharge. Gum chewing is offered as a physiologic and inexpensive method to prevent or reduce post cesarean ileus.